2009
DOI: 10.1007/s12011-009-8402-1
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Exogenous Selenium in Cucumber Seedlings Subjected to Salt Stress

Abstract: The study was conducted in order to determine the effects of exogenous selenium (Se) supply (5, 10, or 20 μM) on the resistance of cucumber (Cucumis sativus L.) cv. Polan F1 seedlings to salt stress (50 mM NaCl). Plant growth was negatively affected by excessive salinity and dry mass production as well as photosynthetic pigments accumulation severely decreased. Se treatments at 5 and 10 μM significantly improved the growth rate and increased the photosynthetic pigments and proline contents in cucumber leaves s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
78
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 38 publications
18
78
1
1
Order By: Relevance
“…Consistent with our results, several studies have also shown that Se supplementation may counteract the accumulation of harmful lipid peroxides in the plant cells [28,30,46]. These results can be attributed to the anti-oxidative effects of Se on plants reported previously [11,12,28].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, several studies have also shown that Se supplementation may counteract the accumulation of harmful lipid peroxides in the plant cells [28,30,46]. These results can be attributed to the anti-oxidative effects of Se on plants reported previously [11,12,28].…”
Section: Discussionsupporting
confidence: 93%
“…However, there was a decrease of MDA content in all the Se treatments salt-stressed melon seedlings relative to NaCl-stressed plants grown without Se addition. MDA content decreased, this could be indicative of Se enhancement salt tolerance and the decline of lipid peroxidation, as proved by Hawrylak-Nowak et al [8], who reported that application of Se decreased MDA content in cucumber.…”
Section: Discussionmentioning
confidence: 63%
“…It might due to higher concentrations of Se decrease protein synthesis and premature death of the plant [6]. HawrylakNowak [8] also reported that 5-10 μM Se resulted in notable increase in roots and shoots biomass.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some plant species grown in Se-enriched media have shown enhanced resistance to certain abiotic stresses, e.g. drought (Kuznetsov et al, 2003;Germ et al, 2007;Yao et al, 2009), salinity (Kong et al, 2005;Djanaguiraman et al, 2005;Hawrylak-Nowak, 2009) and heavy metals (Srivastava et al, 2009;Cartes et al, 2010) stresses. Selenium exerts beneficial effects on growth and stress tolerance of plants by enhancing their antioxidative capacity (Kong et al, 2005;Rios et al, 2009).…”
Section: Introductionmentioning
confidence: 99%